Samogitian Cultural Heritage in Numbers: Ignas Končius’ Statistics of Crosses and Chapels in 1911–1940 - Savoniakaitė, Vida (Tautosakos darbai, 2022)
The article analyzes how studies of the Samogitian crosses and chapels, conducted in 1911–1940 by the physicist and ethnographer Ignas Končius (1886–1975) correlate with the global problematics of statistics and ethnography. Throughout the 19th century and in the beginning of the 20th century, the Lithuanian research on folklore and ethnography followed the canonic trends of statistics in the Russian Empire. While working for the Imperial Russian Geographic Society, the Latvian linguist and ethnographer Eduard Volter (1856–1941) developed his ethnographic-statistical studies aimed at defining the “tribal” constitution of the inhabitants, along with the research of their material culture. The Lithuanian scholar Končius assisted Volter in his fieldwork, absorbing his ideas and making statistical accounts of the Samogitian crosses and chapels in 1911–1940. He presented his discoveries and defined his concept of statistics in seven small books titled “Statistics of Crosses and Chapels under the Samogitian Sky”. The author of the article elucidates the connections between the statistical investigation of the Samogitian cultural heritage by Končius and the scholarly cannons of the Russian Empire, as well as the global ethnographic theory. By using the comparative historical analytical approach, she addresses the following issues: (1) characteristics of the Končius’ statistical investigation of 1912, (2) statistical accounts of the years 1932–1940, and (3) his academic connections. The author concludes that the works of Končius have many similarities with German statistics, Johann Gottfried Herder’s anthropology, and in their own way they reveal the history of Samogitia cultural heritage.